Launch disasters in Bangladesh: a geographical study - Naznin Afrose Huq; Ashraf Mahmood Dewan (Faculty of Social Sciences and Humanities, UKM,Bangi, 2006)
Bangladesh is a riverine country and communication by waterways is of great importance especially in the southern region of the country. From Chandpur southwards, waterway is the only means of transport and so a large number of people has to travel by motor launches in the coastal areas and inland. Since the early 1950's, motor launch services have become popular and in the period 1997-98 there were 1,853 registered launches operating 227 routes. But this important mode is ridden with tragic disasters every year, incurring a heavy toll of human lives. Since 1977, there were 248 motor launch accidents recorded by BIWTA (Bangladesh Inland Water Transport Authority) with a loss of 2,309 1ives, 374 persons injured and 208 persons missing. This paper attempts to roughly trace out the causes and the geographical distribution of the accidents through an analysis of a time series data covering the period between 1977 and 2000. It was found that the most frequent type or cause of launch accidents was collision, followed by foundering and overloading. The least frequent accident types were due to under-water currents, shoals, leaning electricity poles and country boats travelling without lights at night and manned by untrained operators, followed by cyclones. Interestingly, overcrowding did not seem to be the most typical of launch disasters in the country